Plagiarism, Trade-Dress and the Value of Design - Kristensen, Tore; Gabrielsen, Gorm; Wilke, Ricky; Zaichowsky, Judy (Ekonomika, 2002)
The distinctive identity of a brand has enormous commercial importance. When a competitor copies that identity with a cheaper inferior product, it can jeopardize the heavy investment in creating and designing products. The identification of the original versus a plagiarized knockoff is a critical issue in the marketplace. However; even when the identity is clear; a remaining issue is whether consumers are willing to pay a premium price for the original product. We use conjoint analysis to investigate the identification and valuation of an original vs. a copy. The willingness to pay for the original depends on the competence or knowledge of the consumer. We suggest ways of identifying “trade dress” by distinguishing among the utilitarian, systemic or symbolic aspects of a product.